The Effect of Betel Leaf Decoction on Reducing Vaginal Discharge Symptoms in Adolescent Girls at Mts Madinatunnajah, Cirebon City - Laily Rachmawati; Nana Fitriana; Aprilya Tunggo Dewi (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objectives: Vaginal discharge in adolescent girls is often considered a normal health issue. However, if not treated properly, it can interfere with health and comfort. One natural remedy used to treat vaginal discharge is boiled betel leaf water, which is known to have antifungal and antibacterial properties. The purpose of this study was to determine the effect of boiled betel leaf water on reducing vaginal discharge symptoms in adolescent girls at MTs Madinatunnajah in Cirebon City. Methods: This study used a pre-experimental design with a pre-post test approach. The sampling technique used in this study was total sampling. The population in this study consisted of 17 female adolescents in the ninth grade at MTs. Paired test was used for data analysis. Results: The results of this study showed a p-value of 0.000<0.05, which indicates that boiled betel leaf water has an effect on reducing vaginal discharge symptoms in adolescent girls at MTS Madinatunnajah in Cirebon City. Conclusion: Giving boiled betel leaf water can reduce vaginal discharge because its antiseptic, antifungal, and antibacterial properties can help kill germs and bacteria that cause vaginal discharge.